Analisis Ship Resistance Untuk Menentukan Daya Main Engine Kapal - Sulaiman Ali; Fitria Ramadani; Syurkarni Ali; Delly Syahputra (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
Calculation of ship resistance can be done using mathematical calculations. The value of the ship's resistance is needed to determine the power of the ship's main engine, which is formed from the shape of the hull itself. This research is designed to obtain a model using naval architecture software. From the cargo ship model, it will then be calculated to produce the required value of resistance and ship power. The method used in the calculation uses the Compton Method. The maximum speed of the cargo ship is 12.5 knots, resulting in a resistance value of 309.8 Kn with a power of 2671,370 Hp.